2008
DOI: 10.3171/ped/2008/1/6/456
|View full text |Cite
|
Sign up to set email alerts
|

Suboccipital decompression for Chiari malformation–associated scoliosis: risk factors and time course of deformity progression

Abstract: Object Chiari malformation Type I (CM-I) is often associated with scoliosis. It remains unclear which subgroups of patients are most likely to experience progression of spinal deformity after cervicomedullary decompression. The authors' goal was to determine the time frame of curvature progression and assess which patient subgroups are at greatest risk for progression of spinal deformity after surgery. Methods <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 15 publications
1
38
0
1
Order By: Relevance
“…Postoperative changes in syrinx were evaluated with spine MRI obtained during the follow-up period, and they were reported to be resolved (syrinx diameter or extent decreased more than 80 %), improved (syrinx diameter or extent decreased between 20 % and 80 %), static (syrinx diameter or extent changeless to less than 20 %), or aggravated (syrinx increased in diameter or extent more than 20 %) [17,21,22]. A significant change in scoliosis was defined by a criterion of 10°c hange in Cobb's angle on plain spine radiographs during the follow-up evaluation, and the changes were reported as either improved (decrease in Cobb's angle of more than 10°), stabilized (change in Cobb's angle of 10°or less), or aggravated (increase in Cobb's angle of more than 10°) [17,23,24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative changes in syrinx were evaluated with spine MRI obtained during the follow-up period, and they were reported to be resolved (syrinx diameter or extent decreased more than 80 %), improved (syrinx diameter or extent decreased between 20 % and 80 %), static (syrinx diameter or extent changeless to less than 20 %), or aggravated (syrinx increased in diameter or extent more than 20 %) [17,21,22]. A significant change in scoliosis was defined by a criterion of 10°c hange in Cobb's angle on plain spine radiographs during the follow-up evaluation, and the changes were reported as either improved (decrease in Cobb's angle of more than 10°), stabilized (change in Cobb's angle of 10°or less), or aggravated (increase in Cobb's angle of more than 10°) [17,23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Although it remains a matter of contention, syrinx causes scoliosis, and sustained damage to the motor nuclei of ventral horn has been the proposed mechanism [28,33]. It was generally believed that the young spine before maturation is flexible, and FMD before the adolescent growth spurt could restore the spinal curve in young Chiari I malformation patients with syrinx and scoliotic deformities [20,23,[34][35][36]. However, according to this study, syrinx in Chiari I malformation can appear in a relatively short period of time, approximately 3 years old.…”
Section: Surgical Outcomes and Complicationsmentioning
confidence: 99%
“…4,11,25,26,32,35,42 High rates of radiographic syrinx improvement have been reported after PFD with dural opening in pediatric CM-I, with symptom resolution often occurring prior to syrinx resolution and scoliosis improvement often occurring after. [1][2][3][4][5][6][7][8][10][11][12][15][16][17]20,26,27,[29][30][31][32][33][34][35]42,44 In part because syrinx improvement has been noted to occur in the majority of 17,19,36,39 At the 2006 American Society of Pediatric Neurosurgeons meeting, for example, a survey of 50% of the membership demonstrated that for children with a symptomatic CM-I and syrinx, only 4% would perform nondural opening surgery and another 4% would use ultrasound to guide whether to add duraplasty, with the vast majority opting for duraplasty with or without tonsillar resection. 36 However, controversy exists over whether the dura must be opened for successful surgery for pediatric CM-I with or without a syrinx, with good clinical outcomes being reported for a variety of methods.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of syrinx reduction is reported to be in the range of 52-100% following PFD for CM-I [18,20,21,23,24,[26][27][28][29]. Similarly, various series have reported successful treatment of scoliosis after neurosurgical management of CM-I with or without syringomyelia [2,[30][31][32][33]. The rate of improvement in scoliosis curve is reported to be in the range of 20-60% [1,10,30,31,33].…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, various series have reported successful treatment of scoliosis after neurosurgical management of CM-I with or without syringomyelia [2,[30][31][32][33]. The rate of improvement in scoliosis curve is reported to be in the range of 20-60% [1,10,30,31,33]. Overall, there is no consensus on the degree of improvement in scoliosis curve after PFD for CM-I.…”
Section: Introductionmentioning
confidence: 94%